EFFECT OF NIOBIUM ADDITION ON THE ELECTROCHEMICAL AND MECHANICAL PROPERTIES OF TITANIUM ALLOYS AS BIOMATERIALS - Dipodiwiryo, Adam Arlei; Djoko Hadi Prajitno; Raden Dadan Ramdan; Riza Wirawan (Journal of Innovation Research and Knowledge, 2024)
Titanium is a metal known for its high strength, lightweight, and excellent corrosion resistance, making it widely used as a biomaterial in medical applications. To further enhance these properties, particularly corrosion resistance and mechanical strength, niobium (Nb) was added to titanium-aluminum (Ti-Al) alloys. In this study, three alloy compositions, Ti-5Al-10Nb, Ti-5Al-8Nb, and Ti-5Al-6Nb, were fabricated using the Electric Arc Furnace (EAF) method. After the melting process, the specimens were characterized using Scanning Electron Microscopy (SEM) combined with Energy Dispersive Spectroscopy (EDS) to analyze the microstructure and alloying element distribution. X-Ray Diffraction (XRD) was employed to identify the crystalline phases formed in the alloys. Electrochemical testing was performed using the Tafel polarization method to measure corrosion rates, while mechanical testing was conducted using the Vickers hardness test to determine material hardness. The results showed that increasing niobium content in the titanium alloy significantly improved the corrosion resistance and hardness of the specimens. The Ti-5Al-10Nb specimen exhibited the lowest corrosion rate and highest hardness compared to the other specimens. These findings suggest that the addition of niobium can enhance the performance of titanium alloys as biomaterials, particularly for hip joint implant applications.